Improving green emission of Tb3+ ions in BaO‐B2O3‐P2O5 glasses by means of Al3+ ions. (2nd March 2016) - Kalpana, T.; Gandhi, Y.; Sudarsan, V.; Piasecki, M.; Ravi Kumar, V.; Veeraiah, N.
Abstract: BaO‐B2 O3 ‐P2 O5 glasses doped with a fixed concentration of Tb 3 + ions and varying concentrations of Al2 O3 were synthesized, and the influence of the Al 3 + ion concentration on the luminescence efficiency of the green emission of Tb 3 + ions was investigated. The optical absorption, excitation, luminescence spectra and fluorescence decay curves of these glasses were recorded at ambient temperature. The emission spectra of terbium ions when excited at 393 nm exhibited two main groups of bands, corresponding to 5 D3  →  7 Fj (blue region) and 5 D4  → 7Fj (green region). From these spectra, the radiative parameters, viz., spontaneous emission probability A, total emission probability A T, radiative lifetime τ and fluorescent branching ratio β, of different transitions originating from the 5 D4 level of Tb 3 + ions were evaluated based on the Judd‐Ofelt theory. A clear increase in the quantum efficiency and luminescence of the green emission of Tb 3 + ions corresponding to 5 D4  →  7 F5 transition is observed with increases in the concentration of Al2 O3 up to 3.0 mol%. The improvement in emission is attributed to the de‐clustering of terbium ions by Al 3 + ions and also to the possible admixing of wave functions of opposite parities. Copyright © 2016 John Wiley & Sons, Ltd.